Duration of Electrically Induced Atrial Fibrillation Is Augmented by High Voltage of Stimulus with Higher Blood Pressure in Hypertensive Rats - Tomomi Nagayama; Yoshitaka Hirooka; Akiko Chishaki; Masao Takemoto; Yasushi Mukai; Shujiro Inoue; Takuya Kishi; Kenji Sunagawa (International Journal of Hypertension)
Objective. Many previous clinical studies have suggested that atrial fibrillation (AF) is closely associated with hypertension. However, the benefits of antihypertensive therapy on AF are still inconsistent, and it is necessary to explore the factors augmenting AF in hypertensive rats. The aim of the present study was to investigate the correlation between arterial pressure or voltage stimulus and to the duration of electrically induced AF in normotensive or hypertensive rats. Methods. AF was reproducibly induced by transesophageal atrial burst pacing in spontaneously hypertensive rats (SHR) and Wistar-Kyoto rats (WKY). We did the burst pacing at high (20 V) or low (5 V) voltage. Results. Duration of AF did not correlate with systolic blood pressure (SBP) and stimulus voltage in WKY. However, only in SHR, duration of AF with high stimulus voltage significantly correlated with SBP and was significantly longer in high than in low voltage stimulus. Discussion and Conclusion. Duration of AF is augmented by high voltage stimulus with higher blood pressure in SHR.